2012
DOI: 10.1002/jmri.23617
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐controlled, MR‐compatible foot‐pedal device to study dynamics of the muscle tendon complex under isometric, concentric, and eccentric contractions

Abstract: Purpose To design a computer-controlled, MR compatible foot pedal device that allows in vivo mapping of changes in morphology and in strain of different musculoskeletal components of the lower leg under passive, isometric, concentric and eccentric contractions. Materials and Methods A programmable servo-motor in the control room pumped hydraulic fluid to rotate a foot-pedal inside the magnet. Towards validating the performance of the device, six subjects were imaged with gated velocity-encoded phase-contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…For example, a high-speed 3D radial cine phase contrast acquisition method has enabled acceleration factors of up to 11 with adequate SNR for angiography applications (Johnson et al, 2008). Additionally, muscle activation studies have been successfully performed previously involving multiple scans of several minute repeated muscle activations at 40% of maximal voluntary contraction (Sinha et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…For example, a high-speed 3D radial cine phase contrast acquisition method has enabled acceleration factors of up to 11 with adequate SNR for angiography applications (Johnson et al, 2008). Additionally, muscle activation studies have been successfully performed previously involving multiple scans of several minute repeated muscle activations at 40% of maximal voluntary contraction (Sinha et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…This is important for avoiding artifacts due to non-identical repetitions [32]. The strong agreement between the strained mesh and the outline of the TA when the ankle was plantarflexed (0.6±0.2 mm RMS error) indicates good accuracy of the results by demonstrating that the trajectories of the most superficial nodes behaved as expected.…”
Section: Discussionmentioning
confidence: 81%
“…In this study’s sample calculations displacement accuracy was found to improve with systematic error correction but not strain accuracy, indicating that the systematic velocity error generated displacement error but not strain error. This was because the velocity distribution was uniform in this application and sampling error did not apply as it would in vivo (Hodgson et al, 2006; Sinha et al, 2012). The magnitude of this sampling error in vivo is difficult to predict, but should be considered in an error analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional cine Phase Contrast (CPC) is an MRI measurement technique that has been used by several research groups to calculate the distribution of strain in a single plane in skeletal muscles (Finni et al, 2003; Kinugasa et al, 2008; Pappas et al, 2002; Sinha et al, 2012; Zhou and Novotny, 2007). The imaging sequence is used to acquire a temporal sampling of spatial velocity distributions in the muscle over a motion cycle.…”
Section: Introductionmentioning
confidence: 99%